21st-century learning: understanding the language learning strategies with technology literacy among L2 learners - Zuraina, Ali (Universiti Sultan Zainal Abidin, 2022)
Background and Purpose: The study concerns investigating the learning of English in the 21st-century when digital learning platforms were used in assigning writing activities to students. Specifically, the use of the media was related to the Language Learning Strategies (LLS), namely metacognitive, cognitive, and social strategies classified by O'Malley et al. (1985) with the learning in the 21st-century.